Some issues of the thin coal explortion at jsw group mines - Dychko, Artur; Dupliak, Maria (Видавництво НТУ ДП, 2020)
Purpose. Carrying out the research for application of the extraction technologies for thin coal seams at JSW Group mines at economically expedient level. Methodology. Applying the methods of mathematical statistics, as well as the assessment of existing technological solutions in mining, the possibility of technical and technological justification of the thin coal seams mining at an economically feasible level.
Keywords: mining; thing coal seam; technology; technical occupation